ANALYSIS OF THE STATE OF FIRE RESISTANCE PROBLEMS OF REINFORCED CONCRETE STRUCTURES, TAKING INTO ACCOUNT THE TIME AND CONDITIONS OF THEIR OPERATION (Neo Scientific Peer Reviewed Journal, 2026)
This article examines the use of in-kind technical fire resistance surveys of reinforced concrete structures. Its practical significance will allow for the formulation of design proposals that can improve residual strength, reduce residual deformation, and ensure the safety of reinforced concrete elements in industrial facilities.